Awareness Level of Poultry Husbandry Practices by the Poultry Farmers in Imphal West District of Manipur (Indian Journal of Extension Education, 2016)
It has been observed that considerable number of poultry farms has grown up in Imphal district and particularly in Imphal west district of the state. Imphal being the main commercial centre of the state, availability of inputs like superior chicks, feeds, scientific equipments and labours has added momentum to the poultry business. Moreover veterinary services are also readily available with the establishment of veterinary hospital and private veterinary clinics in and around the Imphal city. Hence, there is a great scope for poultry rearing so as to fulfil the egg and meat requirement of the state and also to generate employment opportunities for unemployed youth in general and women section in particular. Thus, every effort should be made to utilize the proven poultry technology so as to increase the efficiency of poultry business in Manipur state. The present study was conducted in Imphal- west district of Manipur. A multi-stage sampling procedure was followed for selection of sub-division; village and respondents Total 120 respondents (poultry farmers) were selected based on proportional random sampling method. The study concluded that majority of the farmers had medium level of knowledge on different aspects of poultry production practices. Education, annual average income, socio-economic status, flock size, extension contact, utilization of mass media and attitude toward poultry rearing were the important factors which have contributed to the knowledge gained by the poultry farmers.